Digital habitus and the transformation of social interaction: a case study of smartphone use among students at man 2 model mataram - Jepri Utomo (Balai Diklat Keagamaan Ambon, 2025)
This study aims to explore digital habitus and the transformation of social interaction in the use of smartphones among students at MAN 2 Model Mataram. The approach is a mixed method, combining quantitative and qualitative methods through a case study design. Data collection instruments include observation, interviews, and questionnaires. The results show that smartphone usage among students is very high, with 56.5% frequently using them at school and 88.9% accessing non-academic content during class hours. Although most students claim to use smartphones for studying, many also use them for entertainment and social media, affecting their concentration and leading to peer pressure. This repeated usage forms a digital habitus, a new dispositional pattern that replaces direct social interaction with screen-based interaction. As a result, social relationships among students become more individualistic and weaken collective values within the school environment. The main contribution of this research lies in strengthening the concept of digital habitus within the educational context and highlighting the importance of digital literacy as a strategy for character development in the technological era. The study recommends that school policies not only restrict but also guide technology’s ethical and educational use.